Small gold nanoparticles for tandem cyclization/reduction and cyclization/hydroalkoxylation reactions - Kristína Plevová; Véronique Michelet; Sylvain Antoniotti (Communications Chemistry)
Abstract With peculiar structural features at the surface of small metal nanoparticles, some discrete sites can display catalytic behaviour similar to what could be observed with mononuclear metal catalysts in solution. We have studied the transfer of two catalytic tandem reactions from homogeneous to heterogeneous conditions. Tandem cyclisation/reduction of ortho-alkynyl benzaldehyde derivatives was successfully achieved with Au nanoparticles over TiO2 (Au NPs/TiO2) in the presence of Hantzsch ester with 45-98% yields for 15 examples (average yield: 70.4%). Similarly, tandem cyclisation/hydroalkoxylation of ortho-alkynyl benzaldehyde derivatives was successfully achieved with Au NPs/TiO2 in methanol or other alcohols with 62-96% yields for 17 examples (average yield: 84.9%). The application potential of this catalytic system was demonstrated with the total synthesis of a bioactive isochromene derivative featuring one of the developed reactions as the key step and the implementation of the tandem cyclisation/hydroalkoxylation in a continuous flow reactor, scaling up the reaction by a factor of 10 without loss of efficiency.